PTS regulation domain‐containing transcriptional activator CelR and sigma factor σ54 control cellobiose utilization in Clostridium acetobutylicum. Issue 2 (9th February 2016) - Nie, Xiaoqun; Yang, Bin; Zhang, Lei; Gu, Yang; Yang, Sheng; Jiang, Weihong; Yang, Chen
Summary: The phosphoenolpyruvate:carbohydrate phosphotransferase system (PTS) regulation domain (PRD)‐containing enhancer binding proteins (EBPs) are an important class of σ 54 ‐interacting transcriptional activators. Although PRD‐containing EBPs are present in many Firmicutes, most of their regulatory functions remain unclear. In this study, the transcriptional regulons of about 50 PRD‐containing EBPs in diverse Firmicutes species are reconstructed by using a comparative genomic approach, which contain the genes associated with utilization of β‐glucosides, fructose/levan, mannose/glucose, pentitols, and glucosamine/fructosamine. We then present experimental evidence that the cel operon involved in cellobiose utilization is directly regulated by CelR and σ 54 (SigL) in Clostridium acetobutylicum . The predicted three CelR‐binding sites and σ 54 promoter elements upstream of the cel operon are verified by in vitro binding assays. We show that CelR has an ATPase activity, which is strongly stimulated by the presence of DNA containing the CelR‐binding sites. Moreover, mutations in any one of the three CelR‐binding sites significantly decreased the cel promoter activity probably due to the need for all three DNA sites for maximal ATPase activity of CelR. It is suggested that CelR is regulated by PTS‐mediated phosphorylation at His‐551 and His‐829, which exerts a positive effect and an inhibitory effect, respectively, on the CelR activity. Abstract : The celCA‐bglB‐celB operon involved in cellobiose utilization is directly regulated by CelR and σ54 in Clostridium acetobutylicum . In the presence of cellobiose, CelR is phosphorylated at His‐551 and dephosphorylated at His‐829, which allows CelR to hydrolyze ATP. σ54 directs the RNA polymerase (RNAP) holoenzyme to bind at the ‐12 and ‐24 promoter elements, while CelR binds to three DNA sites (UAS) and uses the energy from ATP hydrolysis to drive the transcription of cel operon .